Design of interpolation filter in delta modulation technique for multirate digital signal processing: article - Ahmad, Asraf (2009)
Delta Modulation is a simple and robust technique for speech coding implementation and yet offers the best technique for multirate digital signal processing. The performance of digital signal processing and communication system is generally limited by the precision of the digital input signal which is archived at the interface between analog and digital information. This project will focus on designing an Interpolation Filter in Delta Modulation (DM) Technique for Multirate Digital Signal Processing [6]. Method to be used is a kind of waveform coding that is Delta Modulation. This project explores DM because it only used a single bit Pulse Code Modulation (PCM) to achieve digital transmission of analog signal [1]. Therefore, the bits rates associated with DM are lower than conventional PCM. Since DM transmits signals at lower bit rates, the bandwidth consume will reduce. Therefore, this project will require a design of interpolation filter at the receiver. The developed model using the SIMULINK in MATLAB environment will be test using the real speech and the performance of the speech quality can be measured based on objective measurement that is signal to noise ratio (SNR) [1] [8]. There are four different techniques of interpolation filters used in this project. The interpolation factor that were propose in this project are L=2 and L=4. At the end of this project, the interpolation filter in the Delta Modulation system has managed to filter the speech that was transmitted.